Intercultural Competence for Education at all Levels - Rosemary Sage (SMARATUNGGA: JURNAL OF EDUCATION AND BUDDHIST STUDIES, 2023)
Current British education means completing set assignments and exams to examine a prescribed curriculum with little room for personal development and individuality. Passing tests does not guarantee students can apply learning in real situations. Currently, 150 American schools have negotiated portfolios of evidence to universities and employers rather than Grade Point Averages (GPA). Portfolios demonstrate personal, practical and academic achievements more clearly than arbitrary tests. Future education must centre around life-competencies and how to be contributing citizens in our complex multicultural societies, based on individual talents and interests. It must focus on thinking, communication and practical application of knowledge and understanding. This requires reviewing everything we know and recognise about formal learning. therefore the purpose of this paper is to examine this situation in order to reveal the importance of intercultural competence at all levels of education. as for the method used by researchers in order to answer these problems is a mixed method. The results show that we need to make communication a priority to achieve intelligence, insight, and reduce the distance between cultures.